Autoimmune channelopathies. - Buckley, C; Vincent, A (2005)
Autoimmune disorders of the neuromuscular junction remain a paradigm for our understanding of autoimmunity. Since the role of autoantibodies to acetylcholine receptors in the pathogenesis of myasthenia gravis was first recognized in the 1970s, a range of antibody-mediated disorders of the neuromuscular junction have been described, each associated with an autoantibody to a specific ligand-gated receptor, voltage-gated ion channel or related protein. In addition, antibodies to a ganglionic form of acetylcholine receptor have been detected in autoimmune forms of autonomic neuropathy. In the past few years, a role for antibodies in disorders of the CNS has begun to emerge, challenging our previous concepts regarding the blood-brain barrier and the role of the humoral immune system in CNS pathology. Although it has not yet been definitively shown that these CNS conditions are antibody-mediated, the detection of the specific antibody supports a trial of immunosuppressive therapy to which many patients appear to respond. In this article, we review the roles of antibodies to receptors and ion channels in the peripheral and central nervous systems, concentrating on the recently defined autonomic and CNS conditions and on the role of antibody measurement in diagnosis and management.